Динаміка концепції радянського цивільного права та відображення її в основах цивільного законодавства СРСР 1991 р. - Харитонов, Євген Олегович; Харитонов, Евгений Олегович; Haritonov, Evgenij (My University, 2011)
The article examines the changes that occurred in tsyvilistychniy doctrine in recent years of the Soviet Union and their reflection in the Fundamentals of Civil Legislation of the USSR and republics in 1991, which were the highest achievement of the Soviet tsyvilistyky were noticeable step of forming the modern concept of civil law in the states that emerged post-Soviet space (including Ukraine).
Харитонов Є. О. Динаміка концепції радянського цивільного права та відображення її в основах цивільного законодавства СРСР 1991 р. / Є. О. Харитонов // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 313-323.
Keywords: цивілістика; цивілістична доктрина; радянська цивілістика; цивилистика; цивилистическая доктрина; советская цивилистика; civil law; civil doctrine; Soviet civil law